Analysis of Earnings Manipulation Shenanigans in the Financial Statements of PT Garuda Indonesia TBK for the 2017-2021 - Wininatalia Gulo; Dyah Mieta Setyawati (Formosa Journal of Multidisciplinary Research, 2023)
Financial shenanigans are an act that is done intentionally to provide information that is not true and is intentionally done to hide or distort the company's financial performance or financial condition. Earnings manipulation shenanigans are earnings manipulation that occur because companies try to cover up declines in financial performance and even share prices and try to realize high investor expectations for profits when reporting quarterly/annual company financial information. The purpose of this research is to find out the indications of 7 categories of earnings manipulation shenanigans. The data used is the financial statements of PT Garuda Indonesia Tbk for the 2017-2021 period. The analysis technique used is a combination of qualitative and quantitative methods using ratio analysis techniques. The results of this study indicate that there are indications of earnings manipulation shenanigans using 7 categories of identification in the financial statements of PT Garuda Indonesia Tbk but not in every year that becomes the research period. The results of the study found indications of recording income too early and recording fake income in the 2018 financial statements, transferring costs from the current period to the previous or subsequent periods in the 2020 financial statements, and hiding losses and costs in the 2018-2021 financial statements.